Critical illness neuropathy: A clinicopathological case. Issue 2 (27th December 2021) - Tateno, Fuyuki; Sakakibara, Ryuji; Aiba, Yosuke; Nakagawa, Koichi; Sugiura, Yoshiya; Hiruta, Nobuyuki
Abstract: We report a case of an older woman who, after a long‐lasting systemic inflammation in a non‐ICU hospital ward, developed severe neuropathy and mild encephalopathy. Electrophysiology and autopsy findings confirmed the diagnosis of critical illness polyneuropathy, with presumed Wallerian degeneration in the spinal dorsal column.